Representación mental de familia en niños y niñas de 5 años que viven en un centro de acogida residencial (CAR) en Lima Metropolitana - Estremadoyro Aybar, Sara Fabiola (2023)
The absence of parental care significantly impacts the integral development of children, leading to repercussions learning processes and family perceptions. In cases of neglect, wherein a child lacks family support, the State assumes responsibility and refers them to residential care facilities to ensure their well-being and rights. In this present exploratory qualitative study, the mental representation of family was examined among 12 five-year-old children situated within an abandonment context and residing within a foster care center. This investigation was conducted through the elicitation of narratives that emerged when these children were exposed to neutral stimuli, such as images from the Thematic Apperception Test, animal version (CAT-A), and drawings of the family using the Corman technique. The methodology employed thematic content analysis on the collected data, overseen by a psychology professional to ensure the process's validity and appropriateness. Recurrent patterns were identified within the children's perceptions, emotions, and beliefs concerning their experiences with their parents or their absence. The findings reveal that the lack of family bonds hinders the mental representation of both parents and the concept of family itself, thereby attributing negative characteristics. Furthermore, these children undergo negative emotions including fear, a dearth of protection, rejection, and a sense of non-belonging. Additionally, they perceive a threatening reality and exhibit challenges in envisioning an alternative future within the familial context.